Research on the efficiency of replication-based storage mechanism - Xiang-yu LUO; Yun WANG; Xiao-mei CHEN; Fei-fei YUAN; Con LI (Tongxin xuebao)
An algorithm-independent description model was established for the ism, and both efficiency-related and efficiency-independent parameters were identified. Besides,the impact of system scale on efficiency was investigated, and an important observation was obtained that the product of the two utilization ratios (i.e., the utilization ratio of disk space and that of I/O bandwidth) is approximately inversely proportional to the number of nodes contained in the system. The observation was verified through experimental resu reason behind was revealed through theoretical analy-sis. The study provides guidelines for the application of replication-based storage mechanism in engineering, and lays a theoretical foundation for the trade-off between the two utilization ratios and for the prediction of I/O performance in large-scale storage systems.